Detection of optrA and poxtA genes in linezolid‐resistant Enterococcus isolates from fur animals in China. (13th September 2022) - Sun, W.; Liu, H.; Liu, J.; Jiang, Q.; Pan, Y.; Yang, Y.; Zhu, X.; Ge, J.
Abstract: The emergence of linezolid‐resistant (LR) enterococci found in food of animal origin arouses attention, but little is known about LR enterococci in fur animals. A total of 342 Enterococcus faecalis and 265 E. faecium strains isolated from fur animals in China from 2015 to 2017 were investigated to determine if LR enterococci (≥16 μg ml −1 ) are present. Overall, two E. faecalis and 12 E. faecium among these isolates were resistant to linezolid. In addition, all LR isolates were classified as multidrug‐resistant isolates. We further explore the resistance genes of the LR enterococci, four E. faecalis and two E. faecium isolates contained optrA gene. Two of them co‐harboured optrA and poxtA genes. We detected virulence genes in LR enterococci were the following: asa1, cylA, esp, gelE and hyl, among which the highest carrying rate gene was asa1 . Besides, all of the LR enterococci we tested had the biofilm‐forming ability. It is worth noting that we detected a novel ST type ST2010 from E. faecium 82‐2. These data show LR enterococci exist in fur animals and have unique characteristics. Abstract : Significance and Impact of the Study: In this study, we first reported linezolid‐resistant (LR) Enterococcus isolates from foxes and minks in the north of China and explored the resistance mechanism. Notably, linezolid is not allowed for treatment of fur animals in China. Resistance genes may come from the environment or other species. What's more, we found a LR Enterococcus faecium isolate and carrying the optrA gene represented a novel ST type ST2010, indicating an involvement of fur animals in the spread of LR bacteria.